Kathmandu Declaration on Cysticercosis : Towards Eradication - Pant, Basant; Onta, Sharad; Pyakurel, Sushil Nath; Karmacharya, Biraj Man; Kumar Nirmal, Bimal; Flisser, Ana; Lightowlers, Marshall (Annapurna Journal of Health Sciences, 2023)
In December 2018, an international conference on cysticercosis was held in Kathmandu,Nepal with the theme, “Towards Eradication”. With the collaboration and participation of human-health and animal-health related organizations, the culmination of this event was the Kathmandu Declaration on cysticercosisrealizing an urgency to take action for its prevention and management.Of the 10 points mentioned in the declaration, all of the keynote speakers and participants on the conference endorsed the activities on commitment for eliminating cysticercosis, urgedthe government to internalize its primary responsibility and role in controlling cysticercosis, and called for the stakeholders for multisectoral collaboration. The authors believe that this declaration and further action definitely strive towards meeting the theme of the conference to eradicate cysticercosis with collaboration among multiple sectors. Several important strategies are also outlined in this article by expanding the statements on the declaration that must be implemented to achieve the targeted goal.